2022
DOI: 10.3389/fonc.2021.742833
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of PALB2 Mutation and Correlation With Immunotherapy Biomarker in Chinese Non-Small Cell Lung Cancer Patients

Abstract: BackgroundPALB2, a gene in the homologous recombination repair (HRR) pathway of the DNA damage response (DDR), is associated with the efficacy of platinum-based chemotherapy, immunotherapy, and PARP inhibitor therapy in several tumors. However, the PALB2 characteristics, its correlation with immunotherapy biomarker, and the prognostic effect of immunotherapy in non-small cell lung cancer (NSCLC) were unknown.MethodsTumor tissue samples from advanced Chinese NSCLC patients were analyzed by next-generation seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…PALB2 is a gene in the homologous recombination repair (HRR) pathway. Jiexia Zhang et al showed that it may not be a promising prognosis predicator on immunotherapy [20]. DDR pathway alterations in SCLC had limited predictive value for platinum efficacy [21].…”
Section: Discussionmentioning
confidence: 99%
“…PALB2 is a gene in the homologous recombination repair (HRR) pathway. Jiexia Zhang et al showed that it may not be a promising prognosis predicator on immunotherapy [20]. DDR pathway alterations in SCLC had limited predictive value for platinum efficacy [21].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with STK11 or KEAP1 mutations, atezolizumab yielded benefits in mOS compared to docetaxel (7.3 vs. 5.8 mo, adjusted HR 0.70; 95% CI 0.49-0.99), especially in SKmut (STK11-or KEAP1-mutated) patients with FAT3 mutation (HR = 0.06, 95% CI 0.01-0.60) [74]. EPHA mutation was significantly correlated with worse efficacy (p = 0.0186) [75], while PALB2 mutation did not correlate with efficacy of immunotherapy (HR = 1.1, p = 0.75) in the POPLAR and OAK cohorts [76]. Consistent with previous findings, a 5-genomic mutation signature composed of CREBBP, KEAP1, RAF1, STK11, and TP53 mutations was discovered to be more significantly correlated with OS than bTMB score and PD-L1 [77].…”
Section: Specific Genetic Mutationsmentioning
confidence: 99%
“…Furthermore, NSCLC is the most important type of lung adenocarcinoma, making lung adenocarcinomarelated research important [3][4][5][6]. Currently, antitumor drug treatments for lung adenocarcinoma mainly include various small molecule protein kinase inhibitors and cytotoxic chemotherapeutics [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NSCLC is the most important type of lung adenocarcinoma, making lung adenocarcinoma-related research important 3 - 6 . Currently, antitumor drug treatments for lung adenocarcinoma mainly include various small molecule protein kinase inhibitors and cytotoxic chemotherapeutics 7 - 12 . Although these drugs or drug combinations are believed to prolong the lives of patients and improve their quality of life, there are still many shortcomings: (1) the sensitivity of patients to these antitumor drugs is purely individual 13 - 15 ; (2) antitumor drug treatment is prone to drug resistance 13 - 15 ; and (3) the side effects of antitumor drug treatment are very serious 16 .…”
Section: Introductionmentioning
confidence: 99%